Fruta podrida: The Vindication of Life and Death from a Sick, Discarded Body - Fallas Arias, Teresa (2016)
Faced with forgetfulness and lack of memory, Lina Meruane depicts in the novel Fruta podrida [Rotten fruit], the drama lived in Chile with the savage implementation of the market economy, a system that attacked in sinister ways the spaces and bodies of Chileans. In this piece, Meruane disassembles the violent and coercive devices over the bodies, claiming the right to life and death, conjecture from which I explore this novel which I focus from the theoretical perspective of Michel Foucault and Judith Butler, regarding the power and the unequal valuation of the bodies. This is a critique of the official memory that absolved those that were guilty of the decomposition of Chilean society; Meruane dares to speak the unspeakable from an ill body that condemns the network of dehumanizing powers of the neoliberal-dictatorial-patriarchal, network that controls the territory and the bodies, making of Chile a memoryless warehouse.